Composition and predicted functional ecology of mussel-associated bacteria in Indonesian marine lakes - Cleary, Daniel F. R.
In the present study, we sampled bacterial communities associated with mussels inhabiting two distinct coastal marine ecosystems in Kalimantan, Indonesia, namely, marine lakes and coastal mangroves. We used 16S rRNA gene pyrosequencing and predicted metagenomic analysis to compare microbial composition and function. Marine lakes are small landlocked bodies of seawater isolated to varying degrees from the open sea environment. They contain numerous endemic taxa and represent natural laboratories of speciation. Our primary goals were to (1) use BLAST search to identify closely related organisms to dominant bacterial OTUs in our mussel dataset and (2) to compare bacterial communities and enrichment in the predicted bacterial metagenome among lakes. Our sequencing effort yielded 3553 OTUs belonging to 44 phyla, 99 classes and 121 orders. Mussels in the largest marine lake (Kakaban) and the coastal mangrove habitat were dominated by bacteria belonging to the phylum Proteobacteria whereas smaller lakes, located on the island of Maratua, were dominated by bacteria belonging to the phyla Firmicutes and Tenericutes. The single most abundant OTU overall was assigned to the genus Mycoplasma. There were several significant differences among locations with respect to metabolic pathways. These included enrichment of xenobiotic biodegradation pathways in the largest marine lake and coastal mangrove. These locations were also the most enriched with respect to nitrogen metabolism. The presence of genes related to isoquinoline alkaloids, polyketides, hydrolases, mono and dioxygenases in the predicted analysis of functional pathways is an indication that the bacterial communities of Brachidontes mussels may be potentially important sources of new marine medicines and enzymes of industrial interest. Future work should focus on measuring how mussel microbial communities influence nutrient dynamics within the marine lake environment and isolating microbes with potential biotechnological applications.